2022
DOI: 10.1002/ijgo.14552
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of tissue inhibitor of metalloproteinase 3, a protein with inhibitory effects on angiogenesis, are increased in pre‐eclampsia

Abstract: Objective To assess and compare circulating tissue inhibitor of metalloproteinase 3 (TIMP‐3) concentrations between women with pre‐eclampsia and healthy pregnant women. We also aimed to determine the relationships between circulating TIMP‐3 and matrix metalloproteinase 2 (MMP‐2), MMP‐9, TIMP‐1, and TIMP‐2 concentrations in pre‐eclampsia. Methods A primary case–control study included patients with pre‐eclampsia (n = 219) and gestational hypertension (n = 118), healthy pregnant women (n = 214), and non‐pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…However, we identified a higher number of significant differentially methylated probes located on the TIMP-3 promoter, as well as an increased TIMP-3 expression in corresponding placental samples from early-onset PE compared to controls, which denotes DNA methylation of TIMP-3 promoter as an epigenetic mechanism in PE (Cruz et al, 2022). Recently, we found that circulating TIMP-3 is increased in patients with PE compared with healthy pregnancy, and these TIMP-3 levels were positively correlated with MMP-2 and TIMP-1 concentrations in PE (Palei et al, 2022). These findings may contribute to understand the relevance of TIMP-3 in the pathophysiology of PE.…”
Section: Matrix Metalloproteinase (Mmp)-2 and Tissue Inhibitor Of Met...mentioning
confidence: 84%
“…However, we identified a higher number of significant differentially methylated probes located on the TIMP-3 promoter, as well as an increased TIMP-3 expression in corresponding placental samples from early-onset PE compared to controls, which denotes DNA methylation of TIMP-3 promoter as an epigenetic mechanism in PE (Cruz et al, 2022). Recently, we found that circulating TIMP-3 is increased in patients with PE compared with healthy pregnancy, and these TIMP-3 levels were positively correlated with MMP-2 and TIMP-1 concentrations in PE (Palei et al, 2022). These findings may contribute to understand the relevance of TIMP-3 in the pathophysiology of PE.…”
Section: Matrix Metalloproteinase (Mmp)-2 and Tissue Inhibitor Of Met...mentioning
confidence: 84%
“…We found heightened expression of several genes associated with increased PE risk including TNFSF13B, TFPI2, TIMP3, RBM25, IGF2R and CSF1 21,[23][24][25][26] in IFN-EVTs compared with control EVTs (Figure 3e). We also observed increased expression of complement activation components that have specifically been implicated in PE pathogenesis (CFH, CFB, C1R, C1S) in IFN-exposed EVTs 27,28 .…”
Section: Elevated Type I Interferon Limits Endovascular Extravillous ...mentioning
confidence: 91%
“…The regulation of angiogenesis in PE has been extensively studied over recent years, leading to the identification of novel angiogenesis-related PE biomarkers, such as tissue inhibitor of metalloproteinase 3 (TIMP-3) [ 104 ]. As mentioned before, chemerin serum levels are elevated in pre-eclamptic patients.…”
Section: Potential Role Of Chemerin In the Pathophysiology Of Pementioning
confidence: 99%